Diagnóstico socioambiental e gestão participativa de unidades de conservação marinhas: o caso do Parque Estadual Marinho da Pedra da Risca do Meio (Fortaleza, Nordeste do Brasil) - Andrade, Aline Batista de (2015)
The scientific literature on marine protected areas has gaps as social environmental diagnostics and participatory management, in which approach the characterization of stakeholders and their relation to protected areas. In this sense, the overall aim of this research is to provide the social environmental diagnosis and the perception of stakeholders of Marine State Park Pedra da Risca do Meio (PEMPRM). The social environmental diagnosis and the research of perception resulted from: archival work; questionnaires and interviews; and meetings of participation, which occurred in 2013 and 2014. The survey was conducted through questionnaires and interviews. The sample size was 60 stakeholders, which are 30 recreational divers and 30 artisanal fishermen. Data were statistically analyzed using the Chi-Square test (χ²), with 5% significance level. The justifications of the answers were categorized by setting up frequencies for each category. The meetings of participation counted with the direct involvement of 13 artisanal fishermen, and also there was the presence of listener participants. The socioeconomic profile of the recreational divers of PEMPRM is mostly male, with well distributed age group and complete higher education. The profile of artisanal fishers is all male, most of which has aged over 40 years, incomplete elementary school education and dependence on fishing as the sole source of income. Recreational divers said they use mainly compressed air and artificial light. As for fishing tackle, there is the use of hook and line by 100% of fishermen; however, other instruments are also mentioned: “manzuá”, “marambaia”, “caçoeira” and trawl. Divers and fishermen consider PEMPRM as very important protected area and deem also important your cooperation in participatory management of this area. For these actors, PEMPRM promotes the preservation of the marine environment and the benefit to the continued implementation of the recreational diving and artisanal fishing activities in the region. While act in PEMPRM, divers and fishermen compete for space and environmental resources, hereby it has led to conflicts between these two groups of local stakeholders. Regarding the revision of the management category, prevailed ideas that signal to a proposal to adapt PEMPRM for Extractive Reserve (RESEX).